Ultimate bearing capacity analysis of a reactor pressure vessel subjected to pressurized thermal shock with XFEM. (October 2017) - Sun, Xin; Chai, Guozhong; Bao, Yumei
Abstract: Under pressurized thermal shock (PTS), the structure integrity of reactor pressure vessel (RPV) meets a potential challenge. The vicinity of inlet nozzle is the weak link and hazardous area of the vessel. Once crack initiation occurs here, the stress concentration around the crack tip would lead to plastic deformation, crack propagation, and even the failure of the whole structure. Based on ABAQUS, the beltline region around the inlet nozzle was modeled to calculate the response of the transient temperature field and stress strain field. In order to demonstrate the ultimate bearing capacity of the RPV with the critical crack sizes, the dynamic process of crack propagation was simulated with the XFEM. Through the quantitative analysis of the Mises stress and circumferential stress through the wall thickness, the crack propagation paths in different directions were confirmed. The above analysis and calculation provide an important reference for the safety and reliability assessment of RPV. Highlights: Pressurized thermal shock has a great impact on the crack initiation and propagation. The XFEM was used to simulate the dynamic crack propagation around the inlet nozzle. The decrease of the fracture toughness caused by cooling is easy to cause the failure of material.